2012
DOI: 10.1152/ajpregu.00033.2012
|View full text |Cite
|
Sign up to set email alerts
|

Salt sensitivity of nitric oxide generation and blood pressure in mice with targeted knockout of the insulin receptor from the renal tubule

Abstract: To elucidate the role of the insulin receptor (IR) on kidney nitric oxide generation and blood pressure (BP) control, we generated mice with targeted deletion of renal tubule IR using loxP recombination driven by a Ksp-cadherin promoter. Male knockout (KO) and wild-type (WT) littermates (~4 mo old) were transitioned through three 1-wk treatments: 1) low-NaCl diet (0.085%); 2) high-NaCl diet (HS; 5%); and 3) HS diet plus 3 mM tempol, a superoxide dismutase mimetic, in the drinking water. Mice were then switched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…25). Recently, we also showed that this BP elevation was salt sensitive in those mice and possibly due to reduced renal nitric oxide synthase (NOS) activity (50). We believe this phenotype, however, may be a manifestation of reduced InsR in another cell type, perhaps the TAL, as blood pressure was actually slightly but significantly lower in the current model, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…25). Recently, we also showed that this BP elevation was salt sensitive in those mice and possibly due to reduced renal nitric oxide synthase (NOS) activity (50). We believe this phenotype, however, may be a manifestation of reduced InsR in another cell type, perhaps the TAL, as blood pressure was actually slightly but significantly lower in the current model, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Circadian alterations in insulinemia may theoretically influence the circadian pattern of W-ExcR. Indeed, the epithelium of several nephron segments expresses the insulin receptor, which plays a role in water and electrolyte reabsorption (Li et al, 2012;Tiwari et al, 2008;Vidotti et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, renal tubule epithelial cell specific knockout of insulin receptor in mice result in impairment of sodium excretion, decreased urinary Nox excretion and hypertension especially in setting of metabolic syndrome (Tiwari 2008). Moreover, in this animal model decrease in Nox excretion was likely the result of decreased NO production and/or increased oxidative stress (Li 2012). …”
Section: Insulin Metabolic Signaling and Early Kidney Injurymentioning
confidence: 95%
“…Thereby, insulin has a central and complicated role in kidney tissue remodeling through regulation of tubulointerstitial fibrosis and glomerular filtration barrier injury and in kidney function through its regulation of receptor signaling (Chen 2004; Anderson 1996; Welsh 2010; Li 2012). …”
Section: Insulin Metabolic Signaling and Early Kidney Injurymentioning
confidence: 99%